PENGARUH LATIHAN FOTWORK TERHADAP PENINGKATAN KECEPATAN GERAK DALAM PERMAINAN TENIS MEJA PADA SISWA KELAS 11 SMP 15 MEDAN - Bernike, Anof; Barus, Elyezer; Simbolon, Ferdinandus; Sembiring, Jepri; Siregar,S.PD.,M.Or., Dr.Samsuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of footwork training on improving movement speed in table tennis among eighth-grade students of SMP Negeri 15 Medan. The research used an experimental method with a quantitative approach. The research design applied was One Group Pretest-Posttest Design. The sample consisted of 25 students selected using purposive sampling technique. Data collection was carried out through observation, tests, and documentation. The instrument used was a movement speed test in table tennis games. Data analysis techniques included descriptive statistics and hypothesis testing using the t-test. The results showed that the average pretest score was 58.24 and increased to 78.36 in the posttest. The average N-Gain score was 0.48, which was categorized as moderate improvement. The hypothesis testing results indicated that the significance value was smaller than 0.05, meaning that footwork training had a significant effect on improving students’ movement speed in table tennis. Therefore, footwork training can be used as an effective training method to improve students' movement abilities in table tennis learning activities.